Kekerasan Seksual terhadap Anak sebagai Extraordinary Crime: Kajian Kriminologis, Evaluasi Efektivitas Kebijakan Hukum Pidana Berbasis Perlindungan Anak, dan Identifikasi Kesenjangan Implementasi Regulasi di Indonesia - Sarifah Leqsha; Asri Vivi Yanti Sinurat; Junaidi Sholat; Silvi Aulia (Judge : Jurnal Hukum, 2025)
Sexual violence against children constitutes a serious crime with multidimensional and long-term impacts, thereby justifying its classification as an extraordinary crime. This crime not only violates children’s human rights but also threatens the quality of human resources and the sustainability of national development. From a criminological perspective, sexual violence against children is influenced by unequal power relations, social environmental factors, and weaknesses in prevention systems and law enforcement. Indonesia has enacted various criminal law instruments and child protection policies, including Law Number 35 of 2014 on Child Protection and Law Number 12 of 2022 on Sexual Violence Crimes. Nevertheless, the persistently high incidence of sexual violence against children indicates problems related to policy effectiveness and gaps in regulatory implementation at the practical level. This study aims to analyze sexual violence against children as an extraordinary crime from a criminological perspective, to evaluate the effectiveness of child protection–based criminal law policies, and to identify gaps between the normative legal framework and regulatory implementation in Indonesia. The research employs normative legal research using statutory, conceptual, and criminological approaches. The findings reveal that, normatively, criminal law policies have recognized sexual violence against children as a serious crime through the imposition of severe criminal sanctions and the adoption of a victim protection approach. However, in practice, various obstacles remain, including weak inter-agency coordination, limited human resources, insufficient trauma-based recovery services, and a legal culture that has not fully sided with victims. Therefore, strengthening more integrated, victim-oriented, and child-sensitive policies is necessary to bridge the gap between normative law and the realities of law enforcement..